Hydrogen peroxide-responsive micelles self-assembled from a peroxalate ester-containing triblock copolymer. (14th December 2015) - Liu, Chao; Zhu, Xiaowei; Wang, Xiaoli; Miao, Dandan; Liang, Xiaoyu; Wang, Cuiwei; Pang, Liyun; Sun, Hongfan; Kong, Deling; Yang, Jing
Abstract : A novel copolymer was synthesized by using peroxalate esters as linkages and the formed micelles possessed specific H2 O2 responsive reactivity. Abstract : A novel ABA triblock copolymer by using peroxalate esters as linkages was synthesized. In water, this amphiphilic copolymer self-assembled into micelles which were used as drug delivery carriers. When stimulated with hydrogen peroxide, the micelles disassembled to release drugs since the responsive peroxalate ester linkages would be cleaved after the reaction with hydrogen peroxide.